Lire le travail dans les cartes - Roger Cornu (Images du Travail, Travail des Images)
This paper deal with the image of the trades spread through the playing cards, mainly french games. The cards are a strongly coded space which lead to stereotyped pictures.At the beginning of the XIX century, the cards represent the urban tramping trades. In the second part of the century they will show the sedentary craftmen and the shopkeepers. We can find the countryside activities only at the end of the century. The cards will never show pictures of the industrial work and will have difficulties to introduce the technical development. In the last part, the author compare the trumps of the new french tarot pack produced at the end of XIX century with the images of the urban and county life spread in the primary schools at the same period.